Analisis Pengembangan Desa Wisata Berbasis Digital Dalam Meningkatkan Perekonomian Masyarakat Deli Serdang Dalam Kajian Ekonomi Islam - Devi Nadya Hasibuan; Sri Ramadhani; Rahmat Daim Harahap (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Deli Serdang is a district that has natural beauty and cultural diversity that can attract tourists, one of which is the existence of a tourist village. A digital-based tourism village is a village that is managed and developed by utilizing technological developments. This research is qualitative research using interview and observation methods. This study aims to determine the "Development of a Digital-Based Tourism Village in Improving the Economy of the Deli Serdang Community in the Study of Islamic Economics". The results of the study show that in developing a tourist village the local government must cooperate with the community. One of the strategies is through coaching the community and developing it again by making the most of technology, and the government must always pay attention to the village. One example is completing facilities and infrastructure, and maintaining the cleanliness of the environment in tourist villages to support visitor activities so that visitors who come feel comfortable linger in the tourist village area. The concept of tourism in Islam is everything that is entirely framed in Islamic values in every activity and does not conflict with Islamic ethical values. Keywords: tourism village, digital, community economy, Islamic economics